Current Clinical Practice in Cytoreductive Surgery for Advanced Ovarian Cancer: A European Survey. Issue 7 (1st October 2011) - Cibula, David; Verheijen, Rene; Lopes, Alberto; Dusek, Ladislav; ,
Abstract : Background: Surgical treatment of advanced ovarian cancer is a subject of fast development. The aim of this survey was to collect data on current surgical treatment from selected European gynecological oncology centers. Methods: A questionnaire has been sent to gynecological oncology centers from 18 countries across Europe, which are presented on the ESGO Web site. Data were collected on an anonymous basis. All questions were related to the cytoreductive surgery of advanced ovarian cancer. Results: Response rate reached 63%, and data from 17 European countries were analyzed. The median number of new patients with ovarian cancer treated annually in a single centre was 95. Whereas 19% of centers perform infracolic omentectomy only, 81% carry on total omentectomy. Approximately half of the centers conduct appendectomy in all patients with advanced ovarian cancer, 1/3 only if the appendix is macroscopically involved. Lymphadenectomy is carried out in 20% of centers in all cases but in 31% only if no residual disease is achieved. Proportion of patients in whom colorectal resection is performed ranged from less than 5% to more than 40%. Colorectal resection, splenectomy and liver resection are conducted by gynecological oncologist in 27%, 46%, and 12%, respectively. Conclusions: There were substantial differences in the spectrum and complexity of procedures performed in patients with advanced ovarian cancer among large European gynecologic oncology centers. Tendency to more complex surgery was shown in centers with a higher number of cases. Selected bowel and upper abdominal procedures are already performed by gynecological oncologists in large proportion of centers, without existence of well-established postgraduate training program.